Control of Metabolic and Cardiovascular Function by the Leptin–Brain Melanocortin Pathway - do Carmo, Jussara M. (2013)
Obesity is recognized as a major worldwide health problem. Excess weight gain is the most common cause of elevated blood pressure (BP) and markedly increases the risk of metabolic, cardiovascular and renal diseases. Although the mechanisms linking obesity with hypertension have not been fully elucidated, increased sympathetic nervous system (SNS) activity contributes to elevated BP in obese subjects. Recent evidence indicates that leptin and the central nervous system (CNS) melanocortin system, including melanocortin 4 receptors (MC4R), play a key role in linking obesity with increased SNS activity and hypertension. Leptin, a peptide-hormone produced by adipose tissue, crosses the blood–brain barrier and activates brain centers that control multiple metabolic functions as well as SNS activity and BP via the CNS melanocortin system. The crosstalk between peripheral signals (e.g., leptin) and activation of CNS pathways (e.g., MC4R) that regulate energy balance, SNS activity and BP represents an important target for treating obesity and its metabolic and cardiovascular consequences.